2014
DOI: 10.1088/0268-1242/29/11/115014
|View full text |Cite
|
Sign up to set email alerts
|

Broadband 2.4μm superluminescent GaInAsSb/AlGaAsSb quantum well diodes for optical sensing of biomolecules

Abstract: High power, high radiance, broadband light sources emitting in the 2.0-2.5 μm wavelength range are important for optical sensing of biomolecules such as glucose in aqueous solutions. Here we demonstrate and analyze superluminescent diodes with output centered at 2.4 μm (range ~2.2-2.5 μm) from GaInAsSb/AlGaAsSb quantum wells in a separate confinement structure. Pulsed wave output of 1 mW (38 kW/cm2/sr) is achieved at room temperature for 40μm × 2mm devices. Superluminescence is evidenced in superlinear increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In this case a major requirement is amplifiedspontaneous-emission (ASE) power and spectral width. So far, few single-spatial-mode SLD devices have been reported operating > 2 micron wavelength range with output power spectral density higher than 1 μW/nm [5]. In this work we report significant improvement in the GaSb type-I SLD device performance in terms of output power, operating temperature and spectral bandwidth.…”
mentioning
confidence: 63%
“…In this case a major requirement is amplifiedspontaneous-emission (ASE) power and spectral width. So far, few single-spatial-mode SLD devices have been reported operating > 2 micron wavelength range with output power spectral density higher than 1 μW/nm [5]. In this work we report significant improvement in the GaSb type-I SLD device performance in terms of output power, operating temperature and spectral bandwidth.…”
mentioning
confidence: 63%
“…The severe power degradation at longer wavelengths is mainly due to the thermally activated Auger recombination process, 14 which increases with the wavelength, and is the dominant non-radiative recombination process at room temperature. 14,15 Moreover, the SLD carrier density in the active region increases monotonically with the current 16,17 rapidly increasing the Auger recombination rate as this is proportional to the third power of carrier density. 18 In this letter, we report the development of a SLD at 2.55 lm, delivering mW-level average output power.…”
mentioning
confidence: 99%
“…Thus, the performance of SLDs for 2-3 lm spectral range has not met the demands of sensing applications due to very low output powers. 7,8 Recent demonstration in this area includes continuous wave (CW) operation of SLDs at room temperature (RT) with output powers up to 40 mW at 2.05 lm and 5 mW at 2.38 lm. Here, we report a GaSb-based single-transverse mode SLD emitting at $1.9 lm with a maximum output power of $60 mW.…”
mentioning
confidence: 99%
“…Preliminary observations indicated that when using conventional fabrication techniques, the output power for SLDs operating in this wavelength range is limited by facet reflections. 7 Applying low enough anti-reflection coating is challenging but we circumvented this by implementing a chip geometry preventing reflection from facet(s). Our approach enables high power operation even in the absence of anti-reflection coatings.…”
mentioning
confidence: 99%